2021
DOI: 10.3389/fpubh.2021.725505
|View full text |Cite
|
Sign up to set email alerts
|

Early Mental Health and Quality of Life in Discharged Patients With COVID-19

Abstract: Aim: This study aimed to analyze the early mental health (MH) and quality of life (QoL) of discharged patients with coronavirus disease 2019 (COVID-19), which can provide a scientific basis for the further development of intervention programs.Methods: In total, 108 subjects participated in this study, including an experimental group (90 patients diagnosed with COVID-19 from March to April 2020 and hospitalized in Wuhan China Resources & WISCO General Hospital, Wuhan, China, 83.3%) and a control group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
6
0
5
Order By: Relevance
“…This issue has not been as well investigated in acute patients as it has in patients with long-COVID syndrome 22 and discharged patients. 23 Patients affected by COVID-19 complain of several signs and symptoms involving systems other than the respiratory system. Indeed, since the beginning of the pandemic, the heavy impact of SARS-CoV-2 infection on different body systems has been clear, with a negative influence on body functions, activities, and social participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue has not been as well investigated in acute patients as it has in patients with long-COVID syndrome 22 and discharged patients. 23 Patients affected by COVID-19 complain of several signs and symptoms involving systems other than the respiratory system. Indeed, since the beginning of the pandemic, the heavy impact of SARS-CoV-2 infection on different body systems has been clear, with a negative influence on body functions, activities, and social participation.…”
Section: Discussionmentioning
confidence: 99%
“…This issue has not been as well investigated in acute patients as it has in patients with long-COVID syndrome 22 and discharged patients. 23…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Yang et al in 2021, it was established that women with COVID-19 had more severe psychological symptoms than men, and these symptoms also significantly affected the quality of life 21 . According to findings obtained from many epidemiological studies, women carry a higher risk in terms of psychological consequences 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that patients with COVID-19 in the early period after discharge had reduced QoL, higher incidences of anxiety, and more severe anxiety symptoms, particularly women [ 14 ]. In our study, females had an incidence of anxiety and depression three-to-four times higher than that of males 5 months after diagnosis and admission.…”
Section: Discussionmentioning
confidence: 99%